Supervisi Standar Proses Pembelajaran Bahasa Arab di Mts N 1 Bandar Lampung - Rusdiani, Atik (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2016)
The task of supervisors in running the supervision on standard process includes the coordinator, consultant, leader of the group, the evaluators. Object of supervision is the standard process of learning the Arabic language. That process is a national standard relating to the implementation of learning in the educational unit to achieve competency standards. These activities include planning, implementation, assessment, and supervision.This mini research found that supervision in the implementation of the standard process of learning Arabic in MTsN 1 Bandar Lampung run well and achieved the goals that are being formulated